LITERACY CONCEPT PERSPECTIVES IN ENGLISH LANGUAGE LEARNING WITHIN THE EMANCIPATED CURRICULUM - Andriani, Agis; Izzati, Aina Amalia; Syakira, Sitti; Pertamana, Dede; Rosmala, Dewi (Universitas Islam Sumatera Utara (UISU), 2025)
Indonesia’s literacy rate is low, ranking 61st in the PISA survey, 60th in the OECD’s 2016 survey, and 45th in PIRLS 2011. To address this, a Merdeka Belajar curriculum focusing on literacy activities is being implemented. Thus, it is necessary to conduct research related to teachers’ and students’ perspectives of literacy through reading activities in emancipated learning because it can reflect how they understand and experience it. The qualitative case study is used as the research method and involved an English teacher and a 7th-grade student in a junior high school in Tasikmalaya. Data was collected through semi-structured interviews and analyzed using Braun and Clarke (2006) thematic analysis approach. The findings indicate that teachers perceive literacy in English learning as multifaceted, emphasizing reading and writing activities to enhance knowledge. They advocate for literacy skills development through diverse activities, promote independent learning strategies, and employ multimodal approaches, aligning their practices with the principles of the Emancipated Curriculum to empower students. Therefore, further research should explore the impact of English reading literacy activities on students’; English language skills, specifically the four skills, using a quantitative experimental approach to investigate the effects of literacy through reading activities.